Pengaruh Brand Image terhadap minat nasabah dengan Korean Wave sebagai variable intervening (Case Studi Bank Kb Bukopin) - Vajri Rahman, Ahmad (Journal of Science Education and Management Business, 2022)
Brand image means things that can be seen or assessed even before consumers or people use a product or service, including how the brand can meet the social and psychological needs of consumers. Since being acquired by Kokmin Bank, Bank Kb Bukopin has issued a new slogan "Bintang Finansial Indonesia" which can meet all financial needs, and become a reliable financial solution platform in Indonesia. The Bintang Finansial slogan has established Kb Bukopin bank in the competitive banking world in market liberalization competition and has made a significant impact in the banking industry, which previously was largely controlled by state-owned banks. This transformation is not only in the form of slogans, but holistically making changes through technological transformation, product diversification and also communicating through the Korean wave. as a brand ambassador for products. So with this transformation, Bank Bukopin's brand image changed to a foreign private bank owned by Korea. This research aims to find out how brand image influences customer interest. The research uses a quantitative approach by distributing questionnaires to 50 respondents. The research results show that brand image has a significant positive influence on customer interest.